Students’ scientific reasoning on temperature and heat topic: A comparative study of students in urban and rural area - Suryadi, Ahmad; Yuliati, Lia; Wisodo, Hari (Universitas PGRI Kanjuruhan Malang, 2020)
This study aims to describe the scientific reasoning level of students in urban and rural areas on heat and temperature topic. This current study involved 104 students from two schools in urban areas and three schools in rural areas. The instrument used was a six-item essay test. The result showed that the students' scientific reasoning score was still low. However, based on the Mann–Whitney test, the study found that there was a significant difference in scientific reasoning scores between students in urban and rural areas. Both students in urban and rural areas were indicated to have higher proportional reasoning when compared to the other kinds of scientific reasoning. In particular, students’ proportional reasoning in urban areas was higher than in rural areas. The result also showed that probabilistic reasoning and correlational reasoning of students in the rural area tended to be unstable compared to students in the urban area. The implication is that physics teachers in the rural area should make maximum use of the facilities in practicing student reasoning skills.